Pelatihan Pengamanan Data Cyberspace untuk Siswa Sekolah Lanjutan Tingkat Atas - Rini Indrayani (Muria Jurnal Layanan Masyarakat, 2020)
Sosial media is a facility offered by cyberspace where users come from all ages and various types of circles. One of the majority of sosial media users is adolescents under the age of 18 with a profession as students. However, the relatively young age and minimal experience, make these students have insufficient insights about the security in using sosial media. Various cases of cybercrime occur and affect teenagers because of their lack of knowledge about cybersecurity. Therefore training is needed to improve students' insights on the sosial security of the media. The output of this activity is training services for data configuration and settings on various features offered by sosial media. Another outcome is providing insight into the scope of cybersecurity and cybercrime. The method used is to conduct sosial media data configuration training and a short lecture. The expected end result is an increase in human resource knowledge regarding cybersecurity